2015
DOI: 10.1039/c4ra14270e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of zein/quaternized chitosan nanoparticles for the encapsulation and protection of curcumin

Abstract: In this article, we report the successful assembly of nanoparticles (NPs) from a water-soluble chitosan (CS) derivative (N-(2-hydroxyl)propyl-3-trimethyl ammonium chitosan chloride, HTCC) and zein via a low-energy phase separation method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 173 publications
(69 citation statements)
references
References 44 publications
10
59
0
Order By: Relevance
“…Comparing with the spectra of ZNP, the amide I and amide II peaks were shifted to 1652.30 and 1539.01, 1651.77 and 1538.97, 1650.17 and 1539.01, 1650.61 and 1539.94, and 1650.55 and 1538.99 cm −1 in the spectra of Z-Q 30:1 , Z-Q 25:1 , Z-Q 20:1 , Z-Q 15:1 and Z-Q 10:1 , respectively. These findings suggested that another intermolecular force, electrostatic or hydrophobic interactions, might exist between zein and quercetagetin, which were in accordance with previous observations that the interactions between the zein and polyphenols (cranberry procyanidins, curcumin) consisted of hydrogen bonds and hydrophobic interactions (Zou et al, 2012;Liang et al, 2015).…”
Section: Ftir Spectrasupporting
confidence: 90%
“…Comparing with the spectra of ZNP, the amide I and amide II peaks were shifted to 1652.30 and 1539.01, 1651.77 and 1538.97, 1650.17 and 1539.01, 1650.61 and 1539.94, and 1650.55 and 1538.99 cm −1 in the spectra of Z-Q 30:1 , Z-Q 25:1 , Z-Q 20:1 , Z-Q 15:1 and Z-Q 10:1 , respectively. These findings suggested that another intermolecular force, electrostatic or hydrophobic interactions, might exist between zein and quercetagetin, which were in accordance with previous observations that the interactions between the zein and polyphenols (cranberry procyanidins, curcumin) consisted of hydrogen bonds and hydrophobic interactions (Zou et al, 2012;Liang et al, 2015).…”
Section: Ftir Spectrasupporting
confidence: 90%
“…The particles have tendency to aggregate at pH 6 for zein NPs (Fig. 1a) because of the isoelectric pH (pI 6.2) [31], while it was not observed in the solution of 13 coated zein NPs ( Fig. 1b and 1c).…”
Section: Preparation and Stability Of Npsmentioning
confidence: 94%
“…Natural proteins were reported to possess a few antioxidative activity, which depends on the level, sequence and composition of amino acids (Raghavan & Kristinsson, 2008;Tapal & Tiku, 2012). The antioxidative property of Cur is mainly due to donating its hydrogen atom to DPPH (Ak & Gülçin, 2008;Liang et al, 2015). It was observed that the scavenging rate value of free Cur in pH 7 was lower than in pH 6, and the values in both pHs were all sharply decreased after heating because of poor pH and thermal stability, whereas Ly-Cur and Ly-Cur-CMC coacervates can significantly increase the antioxidative effectiveness of Cur at pH 6 before and after heating treatments.…”
Section: Dpph Scavenging Activity Of Cur Binding With Ly-cmc Coacervatesmentioning
confidence: 99%